Relationship between emotional intelligence and leadership styles among leaders - Ng Lai Gek, Elizabeth. (Universiti Malaysia Sarawak (UNIMAS), 2003)
Generally, this project aims to perform a preliminary investigation into relationship between emotional intelligence (EQ) which comprises five (5) characteristics namely; self-awareness, selfregulation, self-motivation, social awareness and social skills and leadership styles (laissez-faire, Iran actional, transformational and autocratic) among leaders. Emotionally intelligent leaders are thought to be happier and more committed to their organization, achieve greater success, perform better in the workplace, take advantage of and use positive emotions to envision major improvements in organizational functioning and use emotions to improve their decision making and instill a sense of enthusiasm, trust and co-operation in other employees through interpersonal relationship. Therefore, research examining the utility of emotional intelligence in predicting effective leaders is gaining its momentum. A case study was conducted in Sarawak Contingent Police Headquarters using a sample of 80 leaders (ranging from position of Assistant Police Commissioner (APC) to Chieflnspector (C/Insp» from various units namely; Communication Unit, Information Technology Unit, Traffic Unit, Transportation Unit, Criminal Investigation Unit, Commercial Crime Unit, Special Branch Unit, Department of Recruitment and Department of Administration And Managerial. Level of emotional intelligence is measured by questionnaire adapted from adapted and modified from the emotional competence framework, which distills findings from MOSAIC competencies for professional and administrative. Leadership styles for transformational leadership were determined by questionnaire modified and adapted from Multifactor Leadership Questionnaire (MLQ) by Bass and Avolio, 1990 as used by Warren Aris in doing the thesis entitled "The Development Of Transformational Leadership Amongst The Iban Community Leaders In The Three Area In Kenowit District Sarawak " and leadership styles of transactional, laissez-faire and autocratic were designed from definitions of leadership styles by Bryrnan (1992), James (1991), Edwin (1991) and Batemen and Snell (1999). The results of the study show that emotional intelligence is associated with two (2) components of leadership styles being studied -transformational and laissez-faire leadership. In contrast, transactional and autocratic leadership were not associated with emotional inte\Jjgence. In other words, there is a significant relationship between emotional intelligence and laissezfaire and transformational leadership styles whilst there is no significant relationship between emotional intelligence and transactional and autocratic leadership styles.